SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SMARTPHONE TERBAIK MENGGUNAKAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING - Fadil Ahmat Zikran; Devni Prima Sari (MUST: Journal of Mathematics Education, Science and Technology, 2026)
The rapid development of smartphone technology has created challenges for university students in selecting devices that best support their academic activities. This study aims to determine the most suitable smartphone for students of the Department of Mathematics, Universitas Negeri Padang, Class of 2022. The decision-making process integrates the Cut Off Point (COP), Rank Order Centroid (ROC), and Fuzzy Simple Additive Weighting (FSAW) methods. The research data were collected through questionnaires distributed to 71 student respondents. Eight mid-range smartphone    alternatives, priced between IDR 3,000,000 and IDR 5,000,000 as of February 2026, were evaluated based on the results of the COP selection process. Of the six initial criteria, five were identified as relevant, namely RAM, battery, price, camera, and operating system, while screen size was eliminated. The criterion weights were determined objectively using the ROC method, whereas the FSAW method was employed to calculate the preference values and rank the smartphone    alternatives. The results indicate that the Poco X7 Pro achieved the highest preference value of 0.92 and was classified as Highly Recommended, followed by the iQOO Z9 5G with a preference value of 0.78 and the Redmi Note 14 Pro 5G with a preference value of 0.64. The findings provide smartphone recommendations that align with the priority needs of students in the Department of Mathematics, Universitas Negeri Padang, and can assist them in selecting devices that support academic activities, including data processing, computational tasks, and digital learning, while remaining within their budget.